Prenatal tobacco and cannabis co‐exposure and offspring obesity development from birth to mid‐childhood. Issue 5 (3rd February 2023) - Kong, Kai Ling; Lee, Jin‐kyung; Shisler, Shannon; Thanos, Panayotis K.; Huestis, Marilyn A.; Hawk, Larry; Eiden, Rina D.
Summary: Background: Although the association between prenatal tobacco exposure and child obesity risk is well‐established, less is known about co‐exposure to tobacco and cannabis. Objective: Determine the relation between prenatal substance co‐exposure and obesity risk. Methods: In a diverse sample of pregnant women, we examined the association between prenatal substance exposure (tobacco‐only and co‐exposure) and child BMI (kg/m 2 ) trajectories from birth to mid‐childhood ( n = 262), overweight/obese status based on BMI percentiles from toddlerhood (24 months) to mid‐childhood (9–12 years), and adiposity outcomes at mid‐childhood (fat mass [kg], fat mass [%] and fat free mass [kg]; n = 128). Given that the major goal of this study was to examine the associations between prenatal substance exposure and child outcomes, we oversampled pregnant women for substance use (with tobacco as the primary focus). Results: Multilevel models demonstrated that children in both exposure groups had a steeper increase in BMI trajectory from birth to mid‐childhood and among co‐exposed children, girls had a steeper increase than boys. Odds ratio of having obesity by mid‐childhood was 12 times higher among those co‐exposed than non‐exposed. Co‐exposure led to significantly greater fat mass and fat mass % compared with no exposure, but exposure to only tobacco was no different than no exposure. Conclusions: Results highlight potentiating effects of cannabis exposure in the context of maternal tobacco use in pregnancy on obesity risk and the importance of multi‐method assessments of obesity.